Answer:
B. (b+3c)+(b+3c)
C. 2(b)+2(3c)
Explanation:
we have
![2(b+3c)](https://img.qammunity.org/2020/formulas/mathematics/college/nx6bmxwtt49m5nfz5gapki89uarycf79x2.png)
Distribute the number 2
![2(b+3c)=2b+2(3c)=2b+6c](https://img.qammunity.org/2020/formulas/mathematics/college/vv4dl1cu73543q1rqf0htq3zrjcu2yyl0h.png)
Verify each case
case A) 3(b+2c)
distribute the number 3
![3(b+2c)=3b+3(2c)=3b+6c](https://img.qammunity.org/2020/formulas/mathematics/college/3y4mzgf3vz4bdnk6q770xsnc507zbb095z.png)
![3b+6c \\eq 2b+6c](https://img.qammunity.org/2020/formulas/mathematics/college/50tdfkcz3eqjh20xiw9m7987f8ywqysd1z.png)
therefore
Choice A is not equivalent to the given expression
case B) (b+3c)+(b+3c)
Combine like terms
![b+3c)+(b+3c)=(b+b)=(3c+3c)=2b+6c](https://img.qammunity.org/2020/formulas/mathematics/college/tdts5vlo1vw5btlbqtfcr9lm8z7avvfiyu.png)
![2b+6c= 2b+6c](https://img.qammunity.org/2020/formulas/mathematics/college/ibfq7xi1z0fmopy7p6lckav6ys0so6xjs1.png)
therefore
Choice B is equivalent to the given expression
case C) 2(b)+2(3c)
Multiply both terns by 2
![2(b)+2(3c)=2b+6c](https://img.qammunity.org/2020/formulas/mathematics/college/6shzw9q4dulydwlh5m6e2x6r10krfm36ti.png)
![2b+6c= 2b+6c](https://img.qammunity.org/2020/formulas/mathematics/college/ibfq7xi1z0fmopy7p6lckav6ys0so6xjs1.png)
therefore
Choice C is equivalent to the given expression